A review of industrial policy in the Northern Cape Province - Setlhabi, Letlhogonolo (My University, 2022)
Although industrial policies have been in place in South Africa for over a decade, their implementation to support and prioritise the manufacturing sector has generally been slow and ineffective, particularly in the province of the Northern Cape (NC), which was the study area. Although the NC has a long history of industrialisation reaching back to the discovery of large diamond deposits in Kimberley in 1867, it has been slow in becoming fully industrialised owing to its weak performance in the manufacturing sector. Moreover, provinces such as Gauteng, the Eastern Cape and KwaZulu-Natal are more advanced in terms of industrialisation. Thus, the researcher aimed to understand the phenomenon by researching the implementation and benefits of industrial policy in the context of the NC. An in-depth investigation revealed several weaknesses in the implementation of policy, which has minimised benefits such as support mechanisms for the manufacturing sector.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Governance to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Industrial policies; Northern Cape; Industrialisation; UCTD; SDG-8: Decent work and economic growth